Analisis Kualitas Pelayanan Berbasis Elektronik dalam Bidang Administrasi Kependudukan pada Kantor Dinas Kependudukan dan Catatan Sipil (Dukcapil) Kota Semarang - Aris Munandar; Entang Adhy Muhtar; Reno Wikandaru (SENTRI: Jurnal Riset Ilmiah, 2026)
This study analyzes the quality of electronic-based public services in the field of population administration at the Department of Population and Civil Registration (Dukcapil) of Semarang City, focusing on the implementation of the digital platform Si D’nok (Semarang Dukcapil Online System). Using a descriptive qualitative approach through interviews, observations, and document analysis, the study explores how digital transformation influences service efficiency, transparency, and accountability. The findings reveal that the adoption of Si D’nok has significantly improved service quality by reducing processing time, enhancing citizen satisfaction, and strengthening population data integration. However, challenges remain, including limited digital literacy among citizens, technical system disruptions during peak hours, and disparities in staff competence across service units. To address these issues, Dukcapil is encouraged to strengthen its digital infrastructure, conduct continuous staff training, and apply good governance principles in service management. Overall, the study concludes that the digital transformation at Dukcapil Semarang represents a progressive step toward achieving efficient, inclusive, and sustainable electronic-based public services.